(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Abstract: To allow easier judgement about successfully 3D printed parts Kumovis develops a proprietary software as guiding instrument for physicians and engineers operating the filament printer R1 to manufacture surgical guides, instruments and implants. The software takes multiple parameters into account to manage the risk of failed print jobs and provides a Go / NoGo decision for the printer operator. Aim of the software is the raise of success rate per printed parts in a regulated market and reduction of failed print jobs.